Kerangka Bisnis Model Canvas pada Industri Halal dalam Perspektif Maqashid Syariah - Nurul Falach, Alifya; Mahsun, Moch; Saiban, Kasuwi (Idarotuna : Journal of Administrative Science, 2024)
The global trend of the halal business and the halal lifestyle should be supported by suitable policies that align with Islamic economic theory. This concept needs to have maslahah according to sharia maqashid. However, there is also a business plan, known as the Business Model Canvas (BMC), that is universally applicable to all types of enterprises. The purpose of this study is to investigate the halal industry's business structure from a maqashid Syariah standpoint using a canvas business model approach. A qualitative literature review is the methodology employed, with data from numerous research publications pertinent to the study issue. Based on Islamic economics in the halal industry and Maqashid Syariah, including maqashid dharuriyah, hajiyat, and tahsiniat, the research results demonstrate that the BMC conceptual framework includes nine elements: customer segments, value proposition, channels, customer relationships, key resources, key activities, revenue streams, and cost structures. at a practical level.